Effect of loading rates of severely thermal-shocked glass fiber/epoxy composites. (March 2017) - Mahato, Kishore Kumar; Rathore, Dinesh Kumar; Dutta, Krishna; Ray, Bankim Chandra
Abstract: Present investigation is aimed to study the effect of short term exposure of thermal-shock conditioning on the mechanical properties of glass/epoxy (GE) composites. The specimens were conditioned at –60 °C temperature for 36 h followed by further conditioning at +70 °C temperature for the same duration. In order to assess the effect of thermal-shock on the mechanical properties, tensile tests of the conditioned and unconditioned specimens were done with various loading rates viz. 1, 10, 100, 500 and 1000 mm/min. The ultimate tensile strength (UTS) as well as strain to failure were found to increase with increase in the loading rates at room temperature; the thermal-shocked conditioned specimens exhibited even higher UTS and failure strain as compared to the unconditioned specimens. It can be stated that different coefficients of thermal expansion during thermal-shock conditioning and significant amount of pre-existing residual stresses govern the stress distribution and ultimately the mechanical properties of glass/epoxy composite. Various dominating modes of failures in the composites were analyzed under scanning electron microscope.